Smart energy management system for zero carbon building / Nuratiyah Musa - Musa, Nuratiyah (2018)
There are evidences that some built environment in developing countries do affect the surrounding because it releases gas which is primarily carbon dioxide (CO2). Thus, in the developing construction industry, sustainability is the priority to ensure that construction is carried out with environmental preservation. 'Zero Carbon' means that the building can generate as much energy through renewable energy or implementation of sustainability tools in construction to affect carbon reduction to the environment. The objectives of the study are to identify the best practice to reduce carbon emission in design and life-cycle impacts, to evaluate the current sustainable building practice, and to propose the new concept for zero carbon building that has been implemented in other countries and has proven to be successful so that the same concept can be applied in Malaysia. The study shows that the gas emission resulting from the usage of the surrounding development and which release Co2 accelerate global warming. There should be improvement in the people's awareness, behavioral and political aspects to achieve carbon reduction. Thus, the new concept should be implemented to produce zero carbon building.